2008
DOI: 10.1002/nml.198
|View full text |Cite
|
Sign up to set email alerts
|

Employee creativity in U.S. and Lithuanian nonprofit organizations

Abstract: This article reports findings from a study designed to test a model of creativity in the United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Amabile (1998) stated that creativity is dependent upon organizational conditions such as freedom of ideas, features of the team, supervisory support and encouragement. Research indicates that when team members have high levels of interpersonal communication, support, and clarity of purpose, team members tend to be very creative and innovative (Jaskyte, 2008).…”
Section: Team Trust Collaborative Culture and Team Creativitymentioning
confidence: 99%
“…Amabile (1998) stated that creativity is dependent upon organizational conditions such as freedom of ideas, features of the team, supervisory support and encouragement. Research indicates that when team members have high levels of interpersonal communication, support, and clarity of purpose, team members tend to be very creative and innovative (Jaskyte, 2008).…”
Section: Team Trust Collaborative Culture and Team Creativitymentioning
confidence: 99%
“…In conclusion, personnel who have high job satisfaction and intrinsic motivation will be highly creative (Füller, 2010). In addition, highly-motivated personnel can produce more creative ideas (Jaskyte, 2008).…”
Section: Job Satisfaction and Motivationmentioning
confidence: 93%
“…Researchers have found that organizational culture is strongly related to creativity (Amabile, 1997;Jaskyte, 2008). Numerous organizational scholars have identified organizational values and norms involved in promoting creativity (Martins and Terblanche, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Applied research is needed to show whether an organization' s efforts to transform its work environment are feasible and productive. In addition, while creativity as an issue is not new to the business field, it is significantly underdeveloped and underresearched in the nonprofit field ( Jaskyte, 2008). Because developing work environments in which creativity can thrive can contribute to increased levels of employee creativity, it is important that the managers of nonprofit organizations have tools that allow them to develop such environments.…”
mentioning
confidence: 99%